Nesting selection of hawksbill turtles in Kepulauan Seribu, Indonesia in response to sea surface temperatures - Nurhaliza Putri Nabila; Mohamad Isnin Noer; Endang Tatang Hidayat; Tessalonica Christianty Andreina (Bioma, 2025)
Hawksbill turtles are listed as a critically endangered species due to decreasing population caused by various factors, including climate change. Sea surface temperatures have significantly contributed to the hatchling success of hawksbill turtles as poikilothermic species; thus, selecting the proper location to nest is crucial for sea turtles. The purpose of this study was to observe the nest selection of hawksbill turtle (Eretmochelys imbricata Linnaeus, 1766) in response to sea surface temperature (SST) in SPTN II, Kepulauan Seribu, Jakarta, Indonesia. SST data were extracted from AQUA-MODIS satellite imagery, while the excess green index as a proxy of canopy cover was quantified using orthomosaics captured by the DJI Mavic Pro 3 at 100 m high. The results showed that SST in the study area fluctuated between 29.02°C and 31.5°C, with the highest temperature recorded in September 2024. There was no significant correlation between SST and sites selected by hawksbill turtles based on vegetation cover features. However, the correlation trend between SST and vegetation cover features indicated the plasticity of hawksbill turtles in selecting more shaded locations as SST increases. This finding highlighted the importance of vegetation cover to mitigate the detrimental effects of rising temperatures in hawksbill turtles' nesting habitats.